2022
DOI: 10.3390/foods11244031
|View full text |Cite
|
Sign up to set email alerts
|

Study on Rice Grain Mildewed Region Recognition Based on Microscopic Computer Vision and YOLO-v5 Model

Abstract: This study aims to develop a high-speed and nondestructive mildewed rice grain detection method. First, a set of microscopic images of rice grains contaminated by Aspergillus niger, Penicillium citrinum, and Aspergillus cinerea are acquired to serve as samples, and the mildewed regions are marked. Then, three YOLO-v5 models for identifying regions of rice grain with contamination of Aspergillus niger, Penicillium citrinum, and Aspergillus cinerea in microscopic images are established. Finally, the relationship… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Compared with the study by Sun et al (2022), the detection target for the experiment in this study was 10 g of rice rather than single grains of rice. By identifying and analyzing the mildewed areas of grouped samples, the obtained results can play a more effective role in practical applications of mold detection in large batches of rice.…”
Section: Analysis Of the Relationship Between Rice Tvc And The Area O...mentioning
confidence: 97%
See 4 more Smart Citations
“…Compared with the study by Sun et al (2022), the detection target for the experiment in this study was 10 g of rice rather than single grains of rice. By identifying and analyzing the mildewed areas of grouped samples, the obtained results can play a more effective role in practical applications of mold detection in large batches of rice.…”
Section: Analysis Of the Relationship Between Rice Tvc And The Area O...mentioning
confidence: 97%
“…( 2016 ) compared the effect of traditional machine learning and the LeNet5 CNN on image recognition of mildewed rice, and the results showed that the early LeNet5 deep learning algorithm had a great advantage in recognition speed and accuracy. However, conventional computer vision methods are unable to detect rice samples with mild mildew contamination, and it is difficult to detect mildly mildewed grains with a total viable bacterial count (TVC) of 10 5 –10 6 CFU/g using methods at conventional observational scales (Sun et al., 2022 ; Zhou et al., 2008 ). Sun et al.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations